Responses of alpine grassland plant communities on Sejila Mountain in the Qinghai-Tibet Plateau to phosphorus addition - Zhang, Xizhe; Ye, Yanhui; Tao, Jiang; Niu, Ziyou; Cui, Zhipan; Li, Jianlin; Han, Yanying (Frontiers in Environmental Science, 2025)
IntroductionAs an important global ecological security barrier, the Qinghai-Tibet Plateau is a key region for exploring how global climate change affects the grassland ecosystem. Therefore, this study explored the mechanism of the impact of intensified atmospheric Phosphorus (P) deposition on the alpine grassland plant communities in Sejila Mountain, Nyingchi, Tibet.MethodsA field experiment with four different gradients of phosphate fertilizer application (0, 50, 75, and 100 kg hm−2 a−1) was designed. The variation patterns of plant morphology, biomass, nutrient content, and stoichiometric ratio characteristics in response to P were systematically analyzed.ResultsP addition significantly affected the total community biomass and root-shoot ratio, showing a trend of initial increase followed by decline (P < 0.05). Additionally, P addition significantly influenced the plant traits (average height, total coverage, and abundance) and aboveground biomass of plant community (Poaceae, Cyperaceae, and Forbs). The plant traits and aboveground biomass of Poaceae and Forbs increased significantly with increasing of P addition levels. At a P addition of 100 kg hm−2 a−1, a decline in these parameters was observed. The total coverage and aboveground biomass of Cyperaceae plants showed a significant downward trend. P addition had limited effects on plant carbon (C) and nitrogen (N) contents and their respective stoichiometric ratios. However, it significantly increased P contents in both aboveground and belowground plant parts (P < 0.05), consequently reducing the C:P and N:P stoichiometric ratios in plants. This effectively enhanced plant P use efficiency.DiscussionThis study highlights the significant role of P addition in shaping the plant community structure and nutrient cycling of alpine grasslands. However, excessive P addition may exacerbate ecological competition among plants, potentially leading to nutritional imbalances and soil environmental degradation.